Comprehensive overview of the current state and impact of cohort studies in newborn screening - Priyanka Sangale; Atul Khadse; Charushila Bhangale (MGM Journal of Medical Sciences)
Inborn errors of metabolism (IEM) are a rare and complex group of inherited disorders, typically observed in infants as autosomal recessive or, less commonly, as X-linked recessive conditions. Newborn screening (NBS) for IEMs can significantly improve prognosis and quality of life through early diagnosis and intervention, marking a significant public health achievement. NBS programs vary by country, but generally include tests for a range of metabolic errors, endocrine disorders, primary immunodeficiency disorders, congenital deafness, congenital heart defects, and cystic fibrosis. Integrating mass spectrometry (MS/MS), genetic sequencing, and emerging technologies such as next-generation sequencing into NBS programs represents a substantial advancement in the field of healthcare. These technologies enable early detection, intervention, and the possibility of personalized treatments through gene therapies. Such advancements are poised to shape the future of NBS, potentially enhancing healthcare outcomes for newborns on a global scale. Neonatal screening is the most well-known and widely implemented proactive and preventative pediatric public health initiative worldwide. It encompasses a comprehensive education system, screening, diagnostic confirmation, management, follow-up, and counseling. This article reviews recent advances in newborn metabolic screening, drawing on the results of various clinical trials and pilot studies.